2012
DOI: 10.1111/j.1600-051x.2012.01855.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Fusobacterium nucleatum in chorionic tissues of high‐risk pregnant women

Abstract: We suggest that F. nucleatum is detected in chorionic tissues of high-risk pregnant women, but not in chorionic tissues of normal pregnant women, and that F. nucleatum induces IL-6 and CRH production via both TLR-2 and TLR-4 in chorion-derived cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…The LPS-induced cytokine response in primary first trimester trophoblasts corresponds with 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 17 findings in other studies (Abrahams et al, 2005, Anton et al, 2012, and TLR4-mediated inflammation is shown associated with PTB in humans (Tateishi et al, 2012) and fetal growth restriction and PE-like symptoms in rats (Cotechini et al, 2014).Whereas primary trophoblasts responded to the TLR2/1 ligand, stimulation with the TLR2/6 ligand failed to induce and equivalent response, reflecting the complexity of the TLR2 signaling system. In trophoblast cell lines, a role for TLR6 in regulating the TLR2/1-response towards cytokine release has been suggested (Abrahams et al, 2008).…”
Section: Discussionmentioning
confidence: 76%
“…The LPS-induced cytokine response in primary first trimester trophoblasts corresponds with 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 17 findings in other studies (Abrahams et al, 2005, Anton et al, 2012, and TLR4-mediated inflammation is shown associated with PTB in humans (Tateishi et al, 2012) and fetal growth restriction and PE-like symptoms in rats (Cotechini et al, 2014).Whereas primary trophoblasts responded to the TLR2/1 ligand, stimulation with the TLR2/6 ligand failed to induce and equivalent response, reflecting the complexity of the TLR2 signaling system. In trophoblast cell lines, a role for TLR6 in regulating the TLR2/1-response towards cytokine release has been suggested (Abrahams et al, 2008).…”
Section: Discussionmentioning
confidence: 76%
“…As in the case of the present study, this bacterium was not detected in all of the samples studied. In a recent study, periodontal pathogens, such as F. nucleatum , P. intermedia , T. forsythia , A. actinomycetemcomitans , and Treponema denticola , were detected in some oral samples from high‐risk pregnant females and normal pregnant females, whereas F. nucleatum alone was detected in chorionic tissues from high‐risk pregnant females 28 . Hence, the detection of one or several species in the gingival sulcus of pregnant females does not necessarily imply their presence in the placenta.…”
Section: Discussionmentioning
confidence: 98%
“…nucleatum is associated with more systemic diseases than other known periodontal pathogens, and has been isolated from more than 10 sites of systemic infection [14], and infection with F . nucleatum has been linked to development of colon cancer [912], adverse pregnancy outcomes [27,28], arterial atherosclerotic plaque growth [7], as well as dementia and brain abscess [14]. The exact role that PD and periodontal pathogens, specifically F .…”
Section: Introductionmentioning
confidence: 99%